Proceedings. 2000 IEEE/RSJ International Conference on Intelligent Robots and Systems (IROS 2000) (Cat. No.00CH37113)
DOI: 10.1109/iros.2000.893174
|View full text |Cite
|
Sign up to set email alerts
|

Virtual passive dynamic walking and energy-based control laws

Abstract: It has been shown that a simplest walker with suitable parameter choice can walk down a gentle slope without any control forces and generate its steady walking pattern utilizing gravity effect automatically. O n the floor, however, the robot cannot exhibit passive walk, so any application methods of passive walk to active walker o n the horizontal floor has not been studied yet. Based o n the observation, in this paper we introduce "virtual passive dynamic walking" with virtual gravity field which acts as a dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
36
0

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(36 citation statements)
references
References 9 publications
0
36
0
Order By: Relevance
“…To realize such quasi-passive dynamic walkers, the actuators should realize both active and passive motions. Although several researchers adopted electrical motors with reduction gears that can provide large torque [4,5], the back-drivability cannot be preserved because of its friction, and therefore, it is difficult to swing the leg in a passive manner. Sugimoto and Osuka adopted direct-drive motors which made the weight of the robot heavy [3].…”
Section: Introductionmentioning
confidence: 99%
“…To realize such quasi-passive dynamic walkers, the actuators should realize both active and passive motions. Although several researchers adopted electrical motors with reduction gears that can provide large torque [4,5], the back-drivability cannot be preserved because of its friction, and therefore, it is difficult to swing the leg in a passive manner. Sugimoto and Osuka adopted direct-drive motors which made the weight of the robot heavy [3].…”
Section: Introductionmentioning
confidence: 99%
“…It was found that the toe-off actuation is advantageous compared to other types of actuation because it decreases the collision loss at heel strike. Other methods for active walking on level ground were also presented [9][10][11]. Studies in passive dynamic walkers have revealed that energy-efficient bipedal robots that can exhibit human-like locomotion could be built without very complicated controllers [12].…”
Section: Introductionmentioning
confidence: 99%
“…in the face of a destabilizing disturbance) with existing ZMP-based strategies. Alternatively, it can be used to increase the narrow regions of attraction which plague minimally actuated passive dynamic walkers [12], [13], [14]. The key concept here is that the FPE-based integration would require minimal joint actuation only to align a swing food appropriately to recover from a potential fall.…”
Section: Introductionmentioning
confidence: 99%